Smoker desaturation during general anaesthesia: a case report - Mohamed, Abdul Hadi; Md Ralib, Azrina; Abdullah, Nor Zamzila; Osman, Ariff (Faculty of Medicine, International Islamic University Malaysia, 2009)
We report a case of sudden hypoxaemia after intubation in a patient who had smoked a few hours prior to a surgical procedure. The cause of his desaturation was not related to bronchial secretions, bronchospasm or obstruction of the upper airways but most likely due to reduced oxygen saturation in the body prior to surgery. We managed to secure the airway and prevent prolonged desaturation by instituting remedial measures. Our conclusion is that cessation of smoking is very important and need to be emphasized in all patients having surgery under general anaesthesia. This applies to emergency cases as well.